Analisis Penyebab Kecelakaan Lalu Lintas di Kota Tanjung Pinang Kepulauan Riau - Heply , Shine Azizah; Siahaan , Dewi Zefanya (Aufklarung: Jurnal Pendidikan, Sosial dan Humaniora, 2022)
Traffic Accidents happens more frequently than we would want.Road accidents cost a lot of lives and property harm.we can see that road accidents cause considerable economic losses to individuals, their families, and to nations as a whole and million people died because road traffic crash. This study aimed to determine risk factors that occurrence of traffic accidents that often happens in Tanjung pinang city.The method in this research is qualitative, namely observation, visual analysis, literature study, and focus group discussion (FGD).Based on Police accident reports record and information about an Traffict accidents in tanjung pinang city,most of the fatal accidents occur due to over speeding.Drivers using aggressive driving behaviors, including speeding, changing lanes frequently, take a quick sideways glance and outride another road users.another factor is ,Traffic rule violations.Traffic rule violations are the major contributors of crashes and fatal crashes .This is because people dont have safety awareness.they not prioritize safety but they prioritize speed and economic factors is the cause the increase in cases and deaths because traffic accidents